Nanotechnology research methods for foods and bioproducts - Padua, Graciela W.; Wang, Qin , 1973- (Wiley-Blackwell, 2012)
Food nanotechnology is an expanding field. This expansion is based on the advent of new technologies for nanostructure characterization, visualization, and construction. Nanotechnology Research Methods for Food and Bioproducts introduces the reader to a selection of the most widely used techniques in food and bioproducts nanotechnology.